Effect of indigenous mycorrhizal fungi on organic osmotic adjusment in soybean under salt stress - Nini Rahmawati; . Rosmayati; . Delvian; Mohammad Basyuni (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Research about influence of indigenous mycorrhizal fungi on organic osmotic adjustment to salinity stress in soybean has been implemented in saline land in Percut Sei Tuan sub district, Regency of Deli Serdang with EC 4-5 mmhos/cm. This study aimed to determine the effect of indigenous mycorrhizalinoculation on organic osmotic adjusment in different soybean varities. This study used Split Plot Design with two plots. The main plot was soybean varieties consist of non-selected Grobogan variety (salt-sensitive variety) and F5 selected Grobogan variety (salt-tolerant variety). Split plot was mycorrhizal inoculumconsists of 7 types of mycorrhizal inoculum namely without inoculum, Glomus sp-1, Glomus sp-2, Glomus sp-3, Glomus sp-4, Glomus sp-5, and combined of all mycorrhizal inoculum. The parameters observed were leaf proline content, reducing sugar and soluble protein. The results showed that leaf proline content,reducing sugar content and soluble protein were significantly different in soybean varieties, mycorrhizal significantly affected leaf proline content, reducing sugar and soluble protein, while the soybean varieties and mycorrhizal interaction significantly affected soluble protein content in leaves.